Experimental investigation of a viscoelastic liner to reduce under helmet overpressures and shock wave reflections - Thomas, Cody J. H.; Dogan, Fatih; Johnson, Catherine E. (Frontiers in Bioengineering and Biotechnology, 2024)
Shock wave overpressure exposures can result in blast-induced traumatic brain injury (bTBI) in warfighters. Although combat helmets provide protection against blunt impacts, the protection against blast waves is limited due to the observed high overpressures occurring underneath the helmet. One route to enhance these helmets is by incorporating viscoelastic materials into the helmet designs, reducing pressures imposed on the head. This study aims to further investigate this mitigation technique against under-helmet overpressures by adding a viscoelastic liner to the inside of a combat helmet. The liner's effectiveness was evaluated by exposing it to free-field blasts of Composition C-4 at overpressures ranging from 27.5 kPa to 165 kPa (4 -24 psi) and comparing shock waveform parameters to an unlined helmet. Blasts were conducted using an instrumented manikin equipped with and without a helmet and then with a helmet modified to incorporate a viscoelastic liner. Evaluation of blast exposure results focused on the waveform parameters of peak pressure, impulse and positive phase duration. The results show that peak overpressure was higher when wearing a helmet compared to not wearing a helmet. However, the helmet with the viscoelastic liner reduced the average peak overpressures compared to the helmet alone. For the lowest overpressure tested, 27.5 kPa, the helmet liner decreased the overpressure on the top of the head by 37.6%, with reduction reaching 26% at the highest overpressure exposure of 165 kPa. Additionally, the inclusion of the viscoelastic material extended the shock waveforms' duration, reducing the rate the shock wave was applied to the head. The results of this study show the role a helmet and helmet design play in the level of blast exposure imposed on a wearer.. The testing and evaluation of these materials hold promise for enhancing helmet design to better protect against bTBI.